2014
DOI: 10.1021/la5032015
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Physical and Covalent Hydrogels Containing pH-Responsive Microgel Particles and Graphene Oxide

Abstract: In this study we mixed low concentrations of graphene oxide (GO) with microgel (MG) particles and formed composite doubly cross-linked microgels (DX MG/GO) gels. The MG particles comprised poly(ethyl acrylate-co-methacrylic acid-co-1,4-butanediol diacrylate) with pendant glycidyl methacrylate units. The MG/GO mixed dispersions formed physical gels of singly cross-linked MGs (termed SX MG/GO), which were subsequently heated to produce DX MG/GO gels by free-radical reaction. The influence of the GO concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 57 publications
0
18
1
Order By: Relevance
“…43 Because CNTs are hydrophobic we postulated that MGs could also be used to disperse CNTs and enable preparation of DX MG/CNT gel composites. In contrast to the DX MG/GO composites 42 we show in the present study that attractive MG-to-CNT interaction are essential for hydrogel composite preparation. Whilst the previously studied DX MG/GO modulus values increased linearly with GO concentration the ductility was constant.…”
Section: Introductioncontrasting
confidence: 84%
See 3 more Smart Citations
“…43 Because CNTs are hydrophobic we postulated that MGs could also be used to disperse CNTs and enable preparation of DX MG/CNT gel composites. In contrast to the DX MG/GO composites 42 we show in the present study that attractive MG-to-CNT interaction are essential for hydrogel composite preparation. Whilst the previously studied DX MG/GO modulus values increased linearly with GO concentration the ductility was constant.…”
Section: Introductioncontrasting
confidence: 84%
“…This observation confirmed that strong, attractive, MG-CNT interactions were present (which is a new result for MG research) and contrasts to our earlier work involving mixed MG/GO dispersions where the two components were repulsive. 42 We established that by increasing the pH to 6.8, where partial MG1 particle swelling occurred (Fig. 1e), the CNTs could be dispersed within viscous mixed MG1/CNT dispersions (Fig.…”
Section: Cnt Dispersion Using Ph-responsive Microgelsmentioning
confidence: 76%
See 2 more Smart Citations
“…Moreover, we have shown that our novel approach using vinyl-functionalised microgels as building blocks and macro-crosslinkers is general by using more than one microgel type to prepare DX MG-colloidosomes. The DX MG colloidosomes were prepared using environmentally benign conditions (pH = 6.8) and DX MGs that are biocompatible 21,22 which indicates suitability for incorporation of biological agents in future work. The DX MG-colloidosomes were strongly pH-responsive and exhibited a major pH-triggered swelling response in the physiological pH region which further supports the view that they have good potential for biomaterial applications, which will be explored in future studies.…”
mentioning
confidence: 99%